Spectroscopic characterization of radicals and radical pairs in fruit fly cryptochrome – protonated and nonprotonated flavin radical‐states. (30th April 2015) - Paulus, Bernd; Bajzath, Csaba; Melin, Frédéric; Heidinger, Lorenz; Kromm, Viktoria; Herkersdorf, Christoph; Benz, Ulrike; Mann, Lisa; Stehle, Patricia; Hellwig, Petra; Weber, Stefan; Schleicher, Erik
<x xml:space="preserve">Abstract</x> Drosophila melanogaster cryptochrome is one of the model proteins for animal blue‐light photoreceptors. Using time‐resolved and steady‐state optical spectroscopy, we studied the mechanism of light‐induced radical‐pair formation and decay, and the photoreduction of the FAD cofactor. Exact kinetics on a microsecond to minutes timescale could be extracted for the wild‐type protein using global analysis. The wild‐type exhibits a fast photoreduction reaction from the oxidized FAD to the FAD− state with a very positive midpoint potential of ~ +125 mV, although no further reduction could be observed. We could also demonstrate that the terminal tryptophan of the conserved triad, W342, is directly involved in electron transfer; however, photoreduction could not be completely inhibited in a W342F mutant. The investigation of another mutation close to the FAD cofactor, C416N, rather unexpectedly reveals accumulation of a protonated flavin radical on a timescale of several seconds. The obtained data are critically discussed with the ones obtained from another protein, Escherichia coli photolyase, and we conclude that the amino acid opposite N(5) of the isoalloxazine moiety of FAD is able to (de)stabilize the protonated FAD radical but not to significantly modulate the kinetics of any light‐inducted reactions.